2023
DOI: 10.1101/2023.01.24.525180
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A time- and space-resolved nuclear receptor atlas in mouse liver

Abstract: The unique functional versatility of the liver is paramount for organismal homeostasis. Both liver development and adult functions are controlled by tightly regulated transcription factor networks, within which nuclear receptors (NRs) regulate essential functions of parenchymal and non-parenchymal cells. Acting as transcription factors sensitive to extracellular cues such as steroidal hormones, lipid metabolites and xenobiotics and modulated by intracellular signaling pathways, NRs orchestrate many aspects of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…Excessive inflammatory cytokines will activate the NF–κB signalling pathway, form a positive feedback inflammatory response, and ultimately aggravate the occurrence of apoptosis. Previous studies have found that PPARβ/δ is highly expressed not only in hepatocytes but also in KCs 31 . We found that activation of PPARβ/δ reduced the expression of inflammatory cytokines in KCs.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Excessive inflammatory cytokines will activate the NF–κB signalling pathway, form a positive feedback inflammatory response, and ultimately aggravate the occurrence of apoptosis. Previous studies have found that PPARβ/δ is highly expressed not only in hepatocytes but also in KCs 31 . We found that activation of PPARβ/δ reduced the expression of inflammatory cytokines in KCs.…”
Section: Discussionsupporting
confidence: 56%
“…PPARβ/δ is highly expressed in hepatocytes and nonparenchymal cells, including Kupffer cells (KCs), liver sinusoidal endothelial cells (LSECs) and hepatic stellate cells (HSCs) 31 . Our study indicated that PPARβ/δ affects the inflammatory response, and KCs are known to be the major effector cells of the inflammatory response in HIRI.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…-catenin is a well-known and evolutionary conserved protein shown to be important in tightjunction formation, cell proliferation, and is integral to the Wnt signaling cascade (102). In the liver, -catenin regulates liver homeostasis, injury repair and tumorigenesis, and protein expression is mainly found in pericentral hepatocytes (103)(104)(105)(106). While a relationship has been identified, the molecular mechanism of -catenin and FXR interactions is undefined.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…hepatocyte FXR function, and due to peri-central protein expression pattern of -catenin, exploration of interzonal and portal hepatocyte FXR should be further studied (103,106).…”
Section: Accepted Manuscriptmentioning
confidence: 99%